City and Water: The Problem of Trauma in the Process of Developing Urban Resilience - Bugno-Janik, Agnieszka; Janik, Marek (Journal of Public Governance, 2021)
Objectives: In the paper, the authors study the socio-cultural, spatial, and functional relationships of city and water in the context of the paradigm shift that is taking place in urban development.Research Design & Methods: The following qualitative methods are used: field observation, participatory observations, transdisciplinary analyses, and case study.Findings: The historical development processes and the resultant collective traumas that have developed in Gliwice were analysed. Some substantial links and correlations have been discovered.Implications / Recommendations: In the sphere of the local cultural background, there are echoes of traumatic events which, to a large extent, have shaped subconscious beliefs and self-defence mechanisms. It is necessary to take this part of reality into consideration while working on city development plans.Contribution / Value Added: The article illuminates the background and mechanisms of some of the processes shaping the relationship between the city and water. Collective traumas play a significant role in these processes, and the fundamental changes that are key to building urban resilience are strongly dependent on working on it attentively. The authors formulate the concept of a trauma network as a significant element of the urban system.Article classification: research articleJEL classification: Y8 Related Disciplines